THE EFFECTS OF DIFFERENT NUTRIENT SOLUTIONS ON THE GROWTH OF BASIL (Ocimum basilicum L.) CULTIVATED UNDER THE CONDITIONS OF GREEN HOUSES - The Hung, Nguyen; Van Quang, Nguyen; Sy Hung, Le; Thi Thuy Chung, Nguyen; Thu Uyen, Bui (Journal of Forestry Science and Technology, 2020)
Hydroponics cultivation has been more and more dominant as the modernization tendency nowadays. However, this method strictly requires precise preparations in making nutrient solutions, which are suitable for corresponding type of plants. Apprehending the fact that Basil is a kind of herb that is capable of creating many benefits for food and medical field, the study team has conducted this project in order to determine the most suitable nutrient solutions for the growth of Basil cultivated in hydroponics. The project is designed with 3 platforms representing 3 nutrient formulas (CT1, CT2, CT3). TDS (Total Dissolved Solutes) and pH are monitored and maintained daily over 3 nutrient types. Simultaneously, criteria, which are harvesting times, heights, weights, and lengths of root, are also recorded and analyzed. About the results of the research, formula CT3 is concluded as the most suitable nutrient type for Basil. This conclusion was demonstrated via that the harvesting times of CT3 are all shorter than the times of the other 2 formulas harvests with the time of each harvest ranging from 10 – 15 days. The average height of CT3’s plants reaches the highest, 40 cm. Whereas, the average height of CT2’s is 39 cm and CT1’s is 34 cm. Likewise, the weights of CT3’s harvests reach more than 1000 gram in 4 out of 8 harvests. Not a single time of harvests of CT1 and CT2 reaches 1000 gram. Similarly, the lengths of roots of CT3’s plants are greater than the other two formulas’ lengths in 8 monitored times.